Analisis Produktivitas pada Eskalator di PT. XYZ Dengan Metode Overall Equipment Effectiveness (OEE) - Nadira Putri Syaharani; Rudy Effendi Lisyanto; Herol (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the operational effectiveness of an escalator using the Overall Equipment Effectiveness (OEE) method and to identify the factors causing performance losses through the Six Big Losses analysis. The research employed a quantitative descriptive approach using operational data, including operating time, downtime, production output, and maintenance records. Data were collected through direct observation, structured interviews, documentation, and literature review. The OEE value was calculated based on its three main components: Availability, Performance, and Quality, and then evaluated against industrial standards to determine the effectiveness level of the escalator. Furthermore, the Six Big Losses method was used to identify the primary sources of efficiency losses and to formulate appropriate improvement recommendations. The results are expected to provide a comprehensive overview of the actual operational performance of the escalator and serve as a basis for developing more effective preventive maintenance strategies to reduce downtime, improve equipment reliability, and optimize operational performance. The proposed recommendations are expected to enhance productivity, extend component service life, and support the implementation of a sustainable maintenance system.